2021
DOI: 10.1155/2021/2230618
|View full text |Cite
|
Sign up to set email alerts
|

Utilization, Determinants, and Prospects of Electronic Medical Records in Ethiopia

Abstract: Background. A lot of effort is being done in the electronic medical record (EMR) system. However, it has not been implemented and used at the expected scale for maximal effectiveness. There is limited evidence on the factors affecting the utilization of EMR in this particular context, which are critical for targeted strategies. Objective. To assess the magnitude and factors affecting the utilization of EMR among health professionals in eastern Ethiopia. Methods. An institutional-based cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 33 publications
4
20
1
2
Order By: Relevance
“…The number of studies with the smallest and largest sample sizes was 412 and 606, respectively. Among the included primary studies, 2 studies were undertaken in the eastern Ethiopia [2,20], 1 in northwest Ethiopia's Amhara region [11], 1 in the Tigray region [21], and 1 in Ethiopia's capital, Addis Ababa [7]. As shown in Table [7], 2015 a To assess the quality of each included study, we used the Joanna Briggs Institute quality assessment tool using 9 criteria.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of studies with the smallest and largest sample sizes was 412 and 606, respectively. Among the included primary studies, 2 studies were undertaken in the eastern Ethiopia [2,20], 1 in northwest Ethiopia's Amhara region [11], 1 in the Tigray region [21], and 1 in Ethiopia's capital, Addis Ababa [7]. As shown in Table [7], 2015 a To assess the quality of each included study, we used the Joanna Briggs Institute quality assessment tool using 9 criteria.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…According to a survey of the comprehensive evaluation of EMR systems in 5 Ethiopian hospitals, only about 31.7% of the participants used EMRs [7]. Similar studies in eastern Ethiopia revealed that EMRs are being used optimally [2]. Another study in the northwestern part of Ethiopia found that only 46.5% of participants used hospital EMR systems [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the government of Ethiopia proposed to implement country-wide EHR which initiated the authors of this research to investigate the readiness level before the actual implementation. Previous progress in digitalization of healthcare such as the implementation of DHIS2, electronic community health information system (e-CHIS), and EMR in a few hospitals indicated that the implementation capability of the country-wide EHR if the pre-implementation activities are handled effectively and supported with research findings [56,[65][66][67].…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, the ministry of health (MOH) deployed EMR in a few Hospitals of central, eastern, and northern parts of Ethiopia as a pilot. But, the plans to scale up those EMRs to other hospitals were failed [65].…”
Section: Introductionmentioning
confidence: 99%